Combatting Cybercrime in West Africa: Assessing the Role of the Economic Community of West African States (ECOWAS) as a Capable Guardian - Ijaiya, Tahir (Governance and Society Review, 2024)
The study examines the role of the Economic Community of West African States (ECOWAS) as a capable guardian in combating cybercrime within West Africa. To do this, the study adopts routine activity theory (RAT) as a theoretical framework. RAT states that crime can only occur when likely offenders and potential targets converge in place and time without a capable guardian, underscoring the vital role of a capable guardian in crime prevention. Relying on secondary data, the study reveals that the ECOWAS has initiated various measures (legislation, workshops, regional meetings, capacity-building programmes, and partnerships) in its bid to play the role of a capable guardian. Furthermore, ECOWAS’s efforts to combat cybercrime have been hampered by several challenges, including poor commitment and inadequate funding for cybercrime and cybersecurity initiatives. The study thus suggests that the ECOWAS ought to invest in improving cybersecurity expertise and cyber law harmonisation within the sub-region.